Evaluation of state forest institutions in Romania based on the 3L model - Hapa, Mihai-Ionut (2019)
Romanian forests account 27.5% of total area and has quite even shares of ownership, 48.5 % state forests and 51.5% private forests. From a total of ~7 million hectares, 3.2 million hectares are state forests managed by State forest administration, 3.8 mil. hectares are managed by private owners or territorial administrative units. This research focuses on the forest policy programs in the contemporaneous context by a performance assessment of the state forest institutions fulfillment of their policy goals. To this end, the 3L Model was using the criteria and indicators approach combined with empirical data from the field (interviews and questionnaires) and available documents, reports, laws etc. The results identify discrepancies between what is on paper and the reality regarding the implementation of forest policy goals, especially regarding cost efficiency of sustained forest stands, as the forests are sustainably managed but with high costs due to lack of forest road infrastructure. Moreover, the forest representation status is clearly challenged, more institutions aspire for the representation of interests in forest which leads to conflicts and bad decision-making. Whilst the state forest administration performance is average, the state authority performance in forestry is relatively low which implies that strengthening of law enforcement is a must in order to mitigate illegal activities in forests and secure property rights protection. A shift towards activating the state forest institutions should be performed by involving all actors in the forest sector and improve the forest policy context through shared representation of the speaker/mediator role. Key words: Romanian forest policy, 3L Model, state forest institutions, management tasks, authority tasks, criteria and indictors, performance evaluation, forest policy.